High genetic diversity among Pseudomonas aeruginosa and Acinetobacter spp. isolated in a public hospital in Brazil - Dias Siqueira, Vera Lúcia [UNESP]; Cardoso, Rosilene Fressatti [UNESP]; de Pádua, Rubia Andreia Falleiros [UNESP]; Caleffi-Ferracioli, Katiany Rizzieri [UNESP]; Helbel, Cesar; Barreto Santos, Adolfo Carlos [UNESP]; Aoki, Elisabeth Eyko; Nakamura, Celso Vataru [UNESP] (Universidade de São Paulo (USP), Conjunto Quimicas, 2013)
In Brazil and other regions of the world, Pseudomonas aeruginosa and Acinetobacter spp. have emerged as important agents of nosocomial infection and are commonly involved in outbreaks. The main objective of the present study was to evaluate the genetic relationship among P. aeruginosa and Acinetobacter spp. isolated from patients in a public university hospital in northwestern Paraná, Brazil, and report their antimicrobial resistance profile. A total of 75 P. aeruginosa and 94 Acinetobacter spp. isolates were phenotypically identified and tested for antibiotic susceptibility using automated methodology. Polymyxin B was tested by disk diffusion for P. aeruginosa. Metallo-b-lactamase (MBL) was detected using a disk approximation test. Genotyping was performed using enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR). Approximately 55% of the P. aeruginosa isolates and 92% of the Acinetobacter spp. isolates were multiresistant, but none were MBL-producers. ERIC-PCR revealed the presence of small clusters of carbapenem-resistant Acinetobacter spp., most likely OXA-type carbapenemase producers. Furthermore, high genetic diversity in P. aeruginosa and Acinetobacter spp. clinical isolates was observed, suggesting that cross-transmission is not very frequent in the studied hospital.
Keywords: Pseudomonas aeruginosa/antimicrobial resistance profile; Pseudomonas aeruginosa/genetic study; Acinetobacter spp./antimicrobial resistance profile; Acinetobacter spp./genetic study; Antimicrobial resistance; Bacterial typing